Assessment of Fiscal Decentralization in Ethiopia: The Case Study of Selected Basic Sectors of Sibu Sire Woreda, East Wollega Zone, Oromia Regional State - GERBABA, DEBELA BEGNA; ALAM, MINHAJ (Universitas Muhammadiyah Yogyakarta, 2019)
This research was conducted on fiscal decentralization in Ethiopia with the case of basic sectors of Sibu Sire Woreda, East Wollega Zone, Oromia Regional State. To attain the objective, researchers relied on primary data followed by secondary sources. To obtain primary data, mixed approach with descriptive design was considered. Probability and non-probability samplings were employed to get the sample of size of 96 whereas non-probability sampling technique was used to select 18 key informants’ interviewees (KIIs) and 7 participants for focus group discussion (FGD). The findings of this research revealed that the principle of fiscal decentralization that is autonomy of sectors is not found in practice. The selected sectors were highly dependent on the allocated regional grant and have very little capacity (null in some sectors) to generate internal revenue. The expenditure responsibilities of the five selected sectors in the Woreda were limited to recurrent expenditures except road sector and to some extent water sector. Data proved the existence of both vertical and horizontal imbalances in terms of revenue generation capacity and percentage of budget share of each sector that ultimately hinder the fiscal autonomy of the sectors in particular and that of the Woreda and local government in general.